Chemical, Thermo-Mechanical and Antimicrobial Properties of DBD Plasma Treated Disinfectant-Impregnated Wipes during Storage - Xinyu Song (Polymers, 2019)
Disinfectant-impregnated wipes are broadly used in hospitals, as an important approach for infection prevention and control. But their ageing performance has rarely been studied. Untreated and Dielectric Barrier Discharge (DBD) plasma pre-treated wiping materials made of nonwoven 100% polyester (W1), nonwoven 55% cellulose/45% polyester (W2) and woven cotton (W3) were impregnated with a quaternary ammonium compound solution (ADBAC) for 30 min, 3, 7, 15, and 30 days of storage time and characterized in term of chemical, thermo-mechanical and antimicrobial efficacy. X-ray photoelectron spectroscopy analysis on the plasma-treated polyester wipes demonstrates the incorporation of reactive oxygen species on the fiber surface. Laser scanning microscopy demonstrates the plasma etching effect in smoothing the surface of the cotton wipe reducing the adsorption of ADBAC. The result showed no significant changes in breaking force and elongation during storage for W1 and W2. However, plasma treatment affects W3 in weft direction reducing the force at break in water and ADBAC treated wipes. Dynamic mechanical analysis results show that ADBAC and plasma treatment have a significant influence in W1 and W3 viscoelastic properties improving the elastic response limiting the polymeric chains mobility and the non-elastic response due to the etching effect, respectively. Overall, the plasma pre-treatment of ADBAC-impregnated wipes is able to enhance the antimicrobial performance and the storage time of polyester-containing wipes.